CREATION OF THE WEB SERVICE Of Ukraine’s NATIONAL NATURAL PARKS AS AN INSTRUMENT FOR ANALYSIS OF TERRITORIES AND DETERMININGISSUES IN ADMINISTRATION AND LAND USE OF TERRITORIES. - Bugaenko, I. S. (GeoScience Engineering, 2018)
The paper focuses on the development and implementation of an electronic cadastre for territories of all National Natural Parks (NPPs); the creation of effective mechanism for registration, monitoring and research of NPP territories, etc., using GIS-technologies. Geographic information systems (GIS) are used by the countries across the world to create conditions for predicted development and sustainable land use to increase the efficiency of management of territories within the NPPs, and the improvement of the natural environment (NE) in leading countries of the world. Keywords: national natural park, map-scheme, Minpryrody, geographic information system, web service, monitoring, GIS-platform https://doi.org/10.2478/gse-2018-0003